Characterization of the temporary epiphyseal arrest of blount in the treatment of genu valgum in Cienfuegos. - Claudia Lissette Martínez Suárez; Carlos Rivero Chau (Universidad de Ciencias Médicas de Granma, 2022)
Introduction: Genu valgum is the most frequent angular deformity in childhood, with spontaneous resolution in most cases, even so, in 10% of cases surgical treatment is required to correct the mechanical axis that modulates growth. Objective: to clinically and epidemiologically characterize patients under 14 years of age diagnosed with Genu valgum who underwent surgery. Methods: a descriptive, retrospective longitudinal observational study was carried out in patients under 14 years of age with diagnosis of Genu valgum, surgically intervened by Blount temporary epiphyseal arrest, between January and July 2019, at the University Pediatric Hospital of Cienfuegos. The universe was constituted by 15 patients. The variables age, sex, reason for consultation, risk factors and postoperative evolution were studied. Results: patients between 12 and 14 years old (46.7 %) and male (53.3 %) predominated. Esthetic deformities were the main reason for consultation (46.7 %) and the risk factor most frequently observed was obesity (40 %). Conclusions: patients with a diagnosis of Genu valgum between the ages of 12 and 14 years represented the highest percentage of those operated on. Esthetic deformities were the main reason for consultation and obesity was the most frequent risk factor.